The Adjustment Of Banyuwangi Culture (Ecoculture Study In Novel By Hasnan Singodimayan) - Iga Bagus Lesmana (Pancaran Pendidikan, 2018)
The creation of literary-work is inseparable from the surrounding culture. If literature is born from culture, then literature is truly an adaptation of a particular culture. Hasan Singodimayan, a cultural observer from Banyuwangi wrote several novels that raised the Banyuwangi regional cultural theme in his works. Hence, this study aims to explain the adjustment of Banyuwangi culture in a novel by Hasnan Singodimayan using ecocultural study. The theory used in this study was Ecoculture Julian H Steward. This descriptive research employed a qualitative approach. Research data were collected through library technique, and then data were analyzed by using content analysis. The findings indicated that the story in the novel by Hasnan Singodimayan adjusted the modified and illogical Banyuwangi culture.